2009
DOI: 10.1002/pd.2205
|View full text |Cite
|
Sign up to set email alerts
|

The attitude of women toward current and future possibilities of diagnostic testing in maternal blood using fetal DNA

Abstract: The attitude of women toward current and future possibilities of diagnostic testing in maternal blood using fetal DNA Kooij, Loes; Tymstra, Tjeerd; van den Berg, Paul Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research database (Pure): http://www.rug.nl/research/portal. For technical reasons the number of authors shown on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 10 publications
4
47
1
Order By: Relevance
“…These findings are in line with other studies where positive attitudes and high interest in NIPT were found among pregnant women. 9,11,14 However, participants in this study realised that the relatively low barrier for the use of NIPT could also have a downside, as it could lead to women feeling less justified to decline this test and thereby jeopardising informed decision-making. This was also shown in a qualitative study by Lewis et al 11 in the UK where participants expressed a concern that women might feel pressured to test when a risk-free blood test is available and offered by trusted healthcare professionals.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These findings are in line with other studies where positive attitudes and high interest in NIPT were found among pregnant women. 9,11,14 However, participants in this study realised that the relatively low barrier for the use of NIPT could also have a downside, as it could lead to women feeling less justified to decline this test and thereby jeopardising informed decision-making. This was also shown in a qualitative study by Lewis et al 11 in the UK where participants expressed a concern that women might feel pressured to test when a risk-free blood test is available and offered by trusted healthcare professionals.…”
Section: Discussionmentioning
confidence: 93%
“…Male partners are often not included in research but as decisions about prenatal testing are preferably made by both partners, and research has shown that men want to be involved in this decision-making process, 13 the views of male partners were also explored in this study. Most studies about pregnant women's attitudes towards NIPT have been based on quantitative methods, 9,10,12,14 which have the advantage of being able to include a large study sample. However, they lack a thorough, in-depth analysis of these attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Here, we evaluate the service users' direct experience of using NIPD for sex-linked genetic conditions and have identified an overwhelmingly positive attitude of participants towards this technology as well as a number of practical and psychological benefits of a test that is easy to perform, is offered relatively early in pregnancy and has no risk of miscarriage. A number of disadvantages were raised.…”
Section: Discussionmentioning
confidence: 99%
“…Another study with pregnant women and female medical students showed the majority were positive about seeing NIPD as an asset in prenatal care, but not for sex selection (Kooij, Tymstra et al 2009). …”
Section: Public Attitudes Towards Prenatal Testing and Nipdmentioning
confidence: 99%